Trackers typhoon tracking software - Agcaoili, Ronnie (1998)
The Philippines is a country frequented by typhoons. Typhoons that sometimes get so strong they leave a trail of death and destruction. Thousands of lives are lost and millions of pesos worth of property are destroyed due to typhoons. We need an early warning system that can pinpoint exactly where and when a typhoon will hit. We also need to know where it is going and how hard it is going to hit. This way people in the vicinity of the coming storm could be forewarned for them to able to take the necessary precautions, even evacuation if needed. This way a lot of lives can be saved and damage to property can be minimized. The Typhoon Tracking Software (TrackerS) attempts to be just that, an early warning system that can predict the path of a tropical cyclone. It will follow the path of the typhoon once it enters the Philippine Area of Responsibility (PAR) and predict the path it is going to trace. This way, people will know ahead of time the necessary precautions to be taken. TrackerS is intended to be used as a typhoon progresses, meaning it can come up with predictions every time the typhoon moves or every so often depending on the user, for as long as the user takes into account that the output of the system has a 24-hour interval. This means that if the user entered a data point, the output will give the probable location of the typhoon after 24 hours. TrackerS will incorporate the use of neural networks in predicting the path of the typhoon instead of purely mathematical computations used to predict the weather. This means it will be a learning system that will be able to adjust to different behaviors of different typhoons to be able to predict its path correctly. It will then learn from this experience to be able to predict more accurately in the future. The TrackerS interface would be that of a land-sea mask with the Philippines in the middle. The path already taken by the typhoon could be viewed, so would be the possible path it is going to take. The graphical representation of the actual typhoon and its movement would also be part of the interface.